An Outline of American government (U.S.International Communication Agency, 1989)
Contents: The constitution: An enduring document; Explaining the constitution: The federalist papers; The executive branch: Powers of the presidency; The legislative branch: The reach of congress; The judicial branch: Interpreting the constitution...